Zabawa a wychowanie dziecka w rodzinie na łamach wybranych czasopism warszawskich przełomu XIX i XX wieku - Bednarz-Grzybek, Renata (Karkonoska Państwowa Szkoła Wyższa, 2011)
Fun is one of children's activity form. From the half of the 19 century it has become an object of many research of educators, psychologists, historians. Fun played an important role in Polish society who was stripped of the personal state system. The topic of entertainment and things connected with toys was taken in social-cultural magazines of the Polish Kingdom in the second half of the19th century and it was also present in next century. The elaboration base of this work are chosen magazines: “Bluszcz”, “Literature feas” and “Family Chronicle”. On their columns, educational problems were discussed in detail, the case of proper child's was placed among it. Manner of spending free time of generation of young Poles could not be indifferent to the whole society. This article presents views of publicists concerning on the advised and criticized manners of spending free time. It also expresses opinions about adviced toys on the columns of press.
Keywords: zabawa; wychowanie; dzieci; Warszawa; czasopisma